A focus on disability is necessary to achieve HIV epidemic control. Issue 4 (April 2022) - Kuper, Hannah; Heydt, Phyllis; Davey, Calum
Summary: Provision of inclusive services and reaching marginalised groups are crucial to achieving the UNAIDS 95-95-95 targets by 2030. However, people with disabilities are often left behind. This gap in HIV care provision is important because more than 1 billion people worldwide have disabilities, including a quarter of people living with HIV. The association between HIV and disability is bidirectional: HIV can cause a range of physical, sensory, and cognitive impairments and people with disabilities are at higher risk of acquiring HIV. People with disabilities often have lower levels of access and adherence to HIV treatment due to barriers with regard to the provision of services (eg, inadequate knowledge among health-care workers and inaccessibility of facilities) and the demand for services (eg, absence of autonomy and awareness of people with disabilities of HIV care needs and service availability). Ultimately, these barriers arise from failures at the system level, including poor governance, leadership, financing, and paucity of data.